3
$\begingroup$

I'm seeing a physics paper about percolation (http://arxiv.org/abs/cond-mat/0202259). In the paper the following asymptotic relation is used without derivation. $$ \sum_{k=0}^{\infty} k P(k) (1 - \epsilon)^{k-1} \sim \left<k\right> - \left<k(k - 1)\right> \epsilon + \cdots + c \Gamma(2 - \lambda) \epsilon^{\lambda - 2}, $$ where $P(k) = c k^{-\lambda}$ with $\lambda > 2$ is a power-law probability mass function of $k$ and the bracket means average. It's the equation number (12) of the paper. I have no idea how to get the relation. Especially, from where does the $\epsilon^{\lambda - 2}$ term come?

$\endgroup$
  • $\begingroup$ I wonder how the right-hand side can (apparently) depend on $k$ while the left-hand side doesn't. Could you clarify what exactly is $\langle k \rangle$ is? $\endgroup$ – Antonio Vargas Feb 19 '14 at 15:50
  • $\begingroup$ Well the $\langle k \rangle$ term is pretty clear. if you expand $u^{n-1}$, since $u=1-\epsilon$ you always get a 1 from each term in the sum. If you collect all such terms you get $\sum P(k) k $ and that's exactly the expectation of $k$. So try collecting the higher order terms. $\endgroup$ – Kai Sikorski Feb 20 '14 at 2:42
  • $\begingroup$ Higher order in $\epsilon$ just to clarify $\endgroup$ – Kai Sikorski Feb 20 '14 at 2:49
1
$\begingroup$

$$ \sum_{k=0}^{\infty} k P(k) (1 - \epsilon)^{k-1} = \sum_{k=0}^\infty k P(k) \left(\sum_{j=0}^{k-1} {k-1 \choose j}(-\epsilon)^j \right)\\ = \sum_{k=0}^\infty k P(k) { k-1 \choose 0} - \sum_{k=0}^\infty k P(k) { k-1 \choose 1} \epsilon + \ldots\\ = \langle k \rangle - \langle k(k-1) \rangle\epsilon + \ldots $$

$\endgroup$
  • $\begingroup$ I made my notation consistent with the article, although I gotta say I find it really ugly to use $k$ as both an index of summation and a random variable in the expectation.. $\endgroup$ – Kai Sikorski Feb 20 '14 at 3:49
  • $\begingroup$ Sorry I don't understand the last term either though $\endgroup$ – Kai Sikorski Feb 20 '14 at 4:08
0
$\begingroup$

I have not been able to see how is coming the $\epsilon^{\lambda - 2}$ term. However, and, may be, this could be a track $$ \sum_{k=0}^{\infty} k P(k) (1 - \epsilon)^{k-1}=\frac{c \Phi (1-\epsilon,\lambda -1,0)}{1-\epsilon}$$ when $P(k) = c k^{-\lambda}$ ($\Phi$ being the the Hurwitz-Lerch transcendent $\Phi(z,s,a)$ function). May be some asymptotic developments ..?

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.